The broadband spectrum of cygnus X-1 - Wilms, Jörn; et al. (2007)
The Black Hole (BH) binary Cygnus X-1 has been observed simultaneously by INTEGRAL, RXTE, and XMM-Newton for four times in November and December 2004, when Cyg X-1 became first observable with XMM-Newton. During these observations the source was found in one of its transitional states between the hard state and the soft state. We obtained a high signal to noise spectrum of Cyg X-1 from 3 keV to 1 MeV which allows us to put constraints on the nature of the Comptonizing plasma by modeling the continuum with Comptonization models as eqpair [3]. Using XMM-Newton we were also able to confirm the presence of a relativistically broadened Fe K alpha line.
Keywords: stars : individual (Cyg X-1); black hole physics